Board Interlock and Firm Performance. - Gangvani, Rohit. (2017)
Abstract: The aim of this paper is to use recent data and update the literature around board interlocks. Using a dataset comprising of 3,720 publicly-listed US firms from 1996-2012, this paper finds that interlocks have a largely negative association with firm performance and that there is indeed evidence to support the view that multiple directorships reflect a strain on directors. The explanation for the results could indeed be that busy directors are ineffectual. However, the key point is that the results in this paper should be interpreted as partial correlations because causality between firm performance and board interlock is difficult to establish.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Economics.; Advisors: Sahar Parsa, and Marcelo Bianconi.; Committee: Enrico Spolaore.; Keyword: Economics.